OGLE-ing the Magellanic System: RR Lyrae stars in the Bridge - Jacyszyn-Dobrzeniecka, Anna M. (The astrophysical journal, 2020)
We use the extended and updated Optical Gravitational Lensing Experiment (OGLE) Collection of Variable Stars to thoroughly analyze the distribution of RR Lyrae stars in the Magellanic Bridge. We use photometric metallicities to derive the absolute Wesenheit magnitude and individual distance of each RR Lyrae star. We confirm results from our earlier study showing that RR Lyrae stars are present in between the Magellanic Clouds, though their three-dimensional distribution more resembles two extended overlapping structures than a strict bridge-like connection. The contours do connect in the southern parts of the Bridge, albeit on a level too low to state that an evident connection exists. To test the sample numerically, we use multi-Gaussian fitting and conclude that there is no additional population or overdensity located in the Bridge. We also try to reproduce results on the putative RR Lyrae Magellanic Bridge stream by selecting RR Lyrae candidates from Gaia Data Release 1. We show that we are not able to obtain the evident connection of the Clouds without many spurious sources in the sample, as the cuts are not able to remove artifacts without eliminating the evident connection at the same time. Moreover, for the first time, we present the Gaia Data Release 2 RR Lyrae stars in the Magellanic Bridge area and show that their distribution matches our results.